(untitled) (Sebha University Conference Proceedings, 2024)
Applying alkanolamines absorption technique in removing H2S and CO2 gases from natural gas, is effective technology for sweetening of natural gas. Exist of acidic gases in natural gas can contribute in many technical problems such as: corrosion, pollution addition to the lack of the heating value of CO2 . In this study, the most often utilized amines in the aqueous solution to extract CO2 and H2S from the natural gas stream are diethanolamine (DEA) and methyldiethanolamine (MDEA). The Mellitah gas facility was selected as a case study for using the MDEA solution as a solvent for the gas sweetening process. To conserve energy for amine regeneration and solution circulation rate, MDEA is more selective than (mono ethanol amine) MEA and DEA. However, MDEA does not directly react with CO2, thus a significant amount of CO2 must be eliminated. In the meanwhile, the Mellitah sweetening unit uses an aqueous solution of MDEA at a 50% concentration to function. On the other hand, using this percentage of amine produces a significant amount of carbon dioxide, which consider highly in comparison with global specifications at 2% of commercial sales. This project firstly applied a 50% wt of MDEA solution by Aspen HYSYS software as a simulator to mimic the Mellitah gas sweetening process. The second step involves putting the suggested enhancement criteria into practice by combining DEA and MDEA and basing it on five situations.